Panagiotis Chr.Stefanides Invited to 4th TECHNIUM International Conference - Recognition of career: The Generator Polyhedron by Panagiotis Stefanides, proposed form of “the other genus-genus of the soul” in Plato’s Epinomis, of the “soul of the world” in Timaeus and of the Republic’s planetary system structure - Stefanides, Panagiotis (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
As I anticipate, it concerns another genus of Polyhedron, a very Special one Ontologically, and this is very important ? understand: “....?????? ?? ?????? ???????? ??? …. ?????, ……., ?? ?? ???? ????? ???? ???? ?????? ?????…..…????? ?????" http://remacle.org/bloodwolf/philosophes/platon/cousin/epinomisgrec.htm [..there are .. five solid bodies…. the other genus which in total has one form …the genus of the soul…] Plato’s Epinomis 981b. In 981a, of this work, Plato states that the composition of, soul and body bares a single form. Similarly, Plato in Timaeus [53 E] refers to the solids having each its own genus and in his Republic makes reference to the Construction of the Universal Planets [XIV 616 E -617A]. Interpretation for ????? genus – form] Proposed By Panagiotis Stefanides is the “Generator Polyhedron”, ohis recent Abstract. Searching, for many years, Plato's Timaeus Work, geometry related to the creation of the world- soul of the world] and presenting it to conferences nationally and internationally, I searched in the Liddell and Scott reference for the word “?????” found in Plato's "Epinomis" 981b Discovered [Invention [ 03 April 2017]. <a href="https://l.facebook.com/l.php?u=https%3A%2F%2Fwww.linkedin.com%2Fpulse%2Fgenerator-polyhedron-platonic-eucleidean-solids-panagiotis-stefanides%2F&h=AT19an3ugjOcJPSM_EMq0LwMdLOoYJbLCdfqDRRVwE3Xp5WWMg63kekvyryQpIuzMt6q_s-vmbVwWqC7OaFZnCFoCJoFq6MeBP42XPTw46OlhY_StyGHFLoU4sUdia32uz6yOmox5ufOWaWMgfjMqvRtTzqNaATJvtqyP6mOIFlp0TihSmpcUA_KPYRAIbykB9pswswyyAiNTqX3I2f14YYxnPKcA9fHLfGF1RCFlsugvVlzngqC4NJosg1pPETkU_EXc1VCzNwy-9_5mgkoTjUQrewaaz9ISIQSfIjZD8QYocl-2cj0S9opoBdKqqYIPjGjnxDCuQ9zvxJJchfDdkr_TxlRzcERMtIxte52rAxWyV80Lw3W_Qex6GnUX9OAqUbNYsltIU2qwM-zFxgtHOcT3juzKRA">https://www.linkedin.com/…/generator-polyhedron-platonic-e…/ . “Generator Polyhedron” refers to the geometric characteristics of this Solid found to be the root upon which other Solid Polyhedra are based i.e. the Platonic/Eucleidean Solids [Icosahedron Dodecahedron etc.] The Geometry of this paper is part of book: [ISBN 978 – 618 – 83169 – 0 - 4], National Library of Greece , 04/05/2017, by Panagiotis Ch. Stefanides.